Synthesis Of rGO/TiO2 Nanowires Derived By Thermal Oxidation Of Titanium As A Photocatalyst For Cr(VI) Reduction - NA, Subagja (2019)
TiO2 nanowires (NWs) were synthesised by thermal oxidation with potassium hydroxide (KOH) catalyst in water vapour. There were two heating steps required in its synthesis; i) KOH deposition, ii) oxidation process. The effect of oxidation temperature, time, KOH presence, and water vapour presence were investigated on the formation of nanowires. It shows that nanowires can grow on oxidised titanium foil with KOH at 550 - 750'C in water vapour. The nanowires formed became longer, thicker, and denser as oxidation temperature increased. However, at 750C, some of nanowires merged with adjacent nanowires resulted in lower areal density. The average length and diameter of nanowire at 750C oxidised sample are 621 nm and 73 nm respectively. As oxidation is time dependent process, the length, diameter, and areal density of nanowire were increased as the oxidation time was longer. Both KOH and water vapour were essential for the growth of nanowire. From X-ray diffraction (XRD), Raman spectroscopy, High Resolution Transmission Electron Microscopy (HR-TEM), X-ray Photoelectron Spectroscopy (XPS) results, the nanowires formed consist of rutile TiO2 and K2Ti6O13 phase or K-rich compound. Growth mechanism of nanowire via thermal oxidation with KOH catalyst in water vapour consists of KOH liquefaction, preferential absorption of constituents (Ti4+, O2-, OH-) in the droplets, nucleation of TiO2 in the droplets, formation of “K-compound-shell”, lateral growth inhibition and c-axis growth due to “K-compound-shell” to form nanowire structure. Reduced graphene oxide (rGO) was deposited onto TiO2 NWs sample by electrophoretic deposition (EPD) method. This method can reduce oxygen-containing group as confirmed by Raman spectroscopy, and XPS results. TiO2 NWs and rGO/TiO2 NWs samples were used as photocatalyst for Cr(VI) reduction under UV and visible light. Under UV, rGO/TiO2 NWs sample performed 100% reduction of 10 mg mL-1 Cr(VI) within 30 minutes. Whereas TiO2NWs sample reduced the same amount of Cr(VI) within 60 minutes. Under visible light, it was only rGO/TiO2 NWs sample that performed 100% reduction of Cr(VI) within 60 minutes, while TiO2 NWs sample did not. In case of rGO/TiO2 NWs irradiated under visible light, photogenerated electrons in rGO can be transferred to TiO2 NWs and Cr(VI) reduction occurred. While under UV, electron – hole pairs formation was happened in TiO2 NWs due to higher photon energy than its band gap. Photogenerated electrons can be transferred spontaneously from TiO2 NWs to rGO to reduce Cr(VI). Depositing rGO on TiO2 NWs creates built-in electric field in TiO2 NWs that can suppress recombination of electron – hole pairs resulted in the enhancement of photoreduction of Cr(VI) performance.